2013
DOI: 10.1103/physrevlett.111.203601
|View full text |Cite
|
Sign up to set email alerts
|

Narrow Optical Homogeneous Linewidths in Rare Earth Doped Nanocrystals

Abstract: A homogeneous linewidth of 85.6±4.4  kHz is reported in 60 nm Eu3+ doped Y2O3 nanocrystals at 1.3 K. This linewidth was measured by two-pulse photon echoes on highly scattering powders using heterodyne detection. Spectral diffusion was also investigated by three-pulse photon echoes and resulted in a limited broadening of the homogenous linewidth of about 250 kHz over 120  μs. Compared to achievable Rabi frequencies, in the range of several MHz, these values show that rare earth doped nanocrystals can be useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 39 publications
5
61
1
1
Order By: Relevance
“…16 The additional dephasing in the ceramics is therefore attributed to magnetic impurities, e.g., very small amounts of transition metal ions or defects. 12,19,30,31 This is in very good agreement with the presence of electron spin impurities (probably transition metal ions) detected by electron paramagnetic resonance for previous samples 12,32 with larger Γ h . For the samples studied here, these impurities could not be detected, presumably because of the higher purity of the Y 2 O 3 starting material (99.999% vs. 99.99%).…”
supporting
confidence: 89%
“…16 The additional dephasing in the ceramics is therefore attributed to magnetic impurities, e.g., very small amounts of transition metal ions or defects. 12,19,30,31 This is in very good agreement with the presence of electron spin impurities (probably transition metal ions) detected by electron paramagnetic resonance for previous samples 12,32 with larger Γ h . For the samples studied here, these impurities could not be detected, presumably because of the higher purity of the Y 2 O 3 starting material (99.999% vs. 99.99%).…”
supporting
confidence: 89%
“…A temperature-dependent broadening of the homogeneous linewidth due to TLS in Eu 3+ :Y 2 O 3 has been observed previously, both in powder and in crystalline fibers. For crystalline domains of 60 nm, α TLS ≈ 18 kHz/K was found [31], and for different fiber crystal samples, 1-15 kHz/K [29]. Thus, the influence of TLS is much weaker in the ceramics than in the crystalline fibers.…”
Section: Temperature Dependence Of the Homogeneous Linewidthsmentioning
confidence: 93%
“…This is highlighted by the studies of different crystal growth techniques that showed that the homogeneous linewidth can vary from 2.4-42 kHz in some crystalline fibers [28,29]. In addition to single-crystal studies, Eu 3+ :Y 2 O 3 has also been the subject of several studies examining the dephasing processes in nanoparticles [30,31]. Therefore, there exists a base of knowledge to draw upon for this material as well as a largely unexplained variation in achievable homogeneous linewidths.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the usual characterization methods employed for REI-doped crystals such as 2PE, SHB, or FID are difficult to perform with powders. Previous measurements on powders have mostly employed detection of fluorescence emission to observe SHB [29,31,59], with direct transmission detection of SHB [49] and 2PE [36,37] only recently being successfully applied to powders. In particular, FID measurements on powders have not been previously reported to our knowledge.…”
Section: Optical Coherence Lifetime Measurementsmentioning
confidence: 99%